Academische studieprent: gezicht : Andromache. - Girard, A.F. (Paris : Reverdin)
Andromaque. Dessinée d'après le tableau original de P. Guérin.
Herkomst: KASK
kunstwerk
Keywords: Guérin, Pierre-Narcisse; Reverdin, Gédéon